RESOLVA AS EQUAÇOES 8(X+1) = 8 - 4 (2X-3)
Soluções para a tarefa
Respondido por
0
8(x+1) = 8 - 4 (2x-3) ⇒ propriedade distributiva
8x+8 = 8-8x +12
8x+8x = 12+8-8
16x = 12
x= 12/16
x = (12÷4)/(16÷4) ⇒ dividir numerador e denominador por 4
x = 3/4
Espero ter ajudado!
8x+8 = 8-8x +12
8x+8x = 12+8-8
16x = 12
x= 12/16
x = (12÷4)/(16÷4) ⇒ dividir numerador e denominador por 4
x = 3/4
Espero ter ajudado!
Respondido por
1
Anexos:
![](https://pt-static.z-dn.net/files/deb/6a6e20799dcbcbb0bb68ba6606c7c8ca.jpg)
Perguntas interessantes
Química,
11 meses atrás
História,
11 meses atrás
Inglês,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás